Gas-liquid interfacial area in the oxygen absorption to oil-in-water emulsions in an airlift reactor - Gómez Díaz, D. (2010)
The present work includes an exhaustive study about gas–liquid interfacial area between gas phase and liquid heterogeneous medium generated in an airlift bioreactor. The system studied is composed by water, methyl ricinoleate (MR), and Tween-80, since it is the base of the medium used for the production of γ-decalactone, a peach-like aroma compound of industrial interest that can be produced biotechnologically through the biotransformation of ricinoleic acid, by the yeast Yarrowia lipolytica. Experimental results allowdescribing the hydrodynamic behaviour of the gas phase into the biphasic medium.